Allosteric activation of vinculin by Talin - Franz, Florian; Tapia-Rojo, Rafael; Winograd-Katz, Sabina; Boujemaa-Paterski, Rajaa; Li, Wenhong; Unger, Tamar; Albeck, Shira; Aponte-Santamaria, Camilo; Garcia-Manyes, Sergi; Medalia, Ohad; Geiger, Benjamin; Gräter, Frauke (Nature Communications, 2023)
The talin-vinculin axis is a key mechanosensing component of cellular focal adhesions. How talin and vinculin respond to forces and regulate one another remains unclear. By combining single-molecule magnetic tweezers experiments, Molecular Dynamics simulations, actin-bundling assays, and adhesion assembly experiments in live cells, we here describe a two-ways allosteric network within vinculin as a regulator of the talin-vinculin interaction. We directly observe a maturation process of vinculin upon talin binding, which reinforces the binding to talin at a rate of 0.03 s−1. This allosteric transition can compete with force-induced dissociation of vinculin from talin only at forces up to 10 pN. Mimicking the allosteric activation by mutation yields a vinculin molecule that bundles actin and localizes to focal adhesions in a force-independent manner. Hence, the allosteric switch confines talin-vinculin interactions and focal adhesion build-up to intermediate force levels. The ‘allosteric vinculin mutant’ is a valuable molecular tool to further dissect the mechanical and biochemical signalling circuits at focal adhesions and elsewhere.